Juan Ginés de Sepúlveda, Bartolomé de Las Casas, Aristotelian concept of slavery - Rokyta, Jan (Univerzita Pardubice, 2018)
The topic of this article is the concept of slavery in Spanish thinkers related to the original population of South America in 16th century. An introduction is devoted to Aristotle´s concept of slavery because it played an important role in the perception of Indians in Juan Gines de Sepúlveda. Furthermore, thinkers denying the validity of slavery in relation to Indians are mentioned, like Bartolomé de Las Casas. The view of slavery here is influenced by the theory of natural rights and linked also to the question of legitimacy of war and legitimacy of social institutions of Indians.
Juan Gines de Sepúlveda, Bartolomé de Las Casas, aristotelské pojetí otroctví
Keywords: Slavery; natural law; legitimacy of war; Otroctví; přirozené právo; legitimizace války